3004 Effects of Early Life Stress on Adult Behavioral and Neural Outcomes in Rats. (27th March 2019) - Moussa-Tooks, Alexandra; Mackie, Ken; Green, John; Bartolomeo, Lisa; Gimeno, Alex; Larson, Eric; Bradshaw, Heather; Leishman, Emma; O'Donnell, Brian; Hetrick, William
Abstract : OBJECTIVES/SPECIFIC AIMS: Early life stress is known to greatly impact neurodevelopment during critical periods, conferring risk for various psychopathologies, including the onset and exacerbation of schizophrenia and anxiety disorders. The endocannabinoid system is highly integrated into the stress response and may be one means by which early life stress produces such deleterious effects. Using a naturalistic, ecologically valid animal model, this study explored interactions between the stress response and endocannabinoid systems within the cerebellum, a region dense with the CB1 endocannabinoid receptors and shown to be susceptible to stress. METHODS/STUDY POPULATION: This study explored behavioral and neural impacts of early life stress in Long-Evans rats reared with or without limited access to bedding material during postnatal day (PND) 2-9. Corticosterone (CORT) levels were measured at PND8 and 70. During PND50-70, rats were assessed on Novel Object Recognition to test memory, Rotarod to evaluate cerebellar integrity, Elevated Plus Maze to assay anxiety, Social Preference, and Eyeblink Conditioning, a cerebellar-dependent and endocannabinoid-mediated task. Lipid analysis was performed on PND70 tissue samples of cerebellar interpositus (IP) nucleus via high-performance liquid chromatography and tandem mass spectrometry. RESULTS/ANTICIPATED RESULTS: Both male and female rats experiencing early life stress exhibited significantly impaired recognition memory (N = 16-20/group). Female rats having undergone stress exhibited decreased social preference compared to normally reared females (N = 11/group). Stressed males showed facilitated eyblink conditioning compared to normally reared males (N = 7-9/group). There were no group differences in rotarod or elevated plus maze performance or CORT levels at PND8 or 70 across rearing groups. At PND70, male rats experiencing early life stress exhibited a significant decrease in 2-arachidonoyl glycerol (2-AG) and arachidonic acid levels in the IP nucleus compared to normally reared males (N = 8-9/group). Compared to normally reared females, those experiencing early life stress exhibited a significant increase in prostaglandin E2 levels in the IP nucleus (N = 6-7/group). DISCUSSION/SIGNIFICANCE OF IMPACT: Early life stress, induced by limited bedding, resulted in sex-specific behavioral and lipid impairments. Results suggest that stress causes long-term alterations in endocannabinoid dynamics in males in the cerebellar IP nucleus and sex-related lipids in female cerebellum. These changes may contribute to observed long-term behavioral aberrations. Moreover, findings suggest these behavioral changes may be the result of negative-feedback dysfunction (as evidenced by decreased endocannabinoids in males) or increased neural inflammation or proliferation (as evidenced by increased prostaglandins in females). Future analysis will quantify mRNA and protein for cannabinoid receptors to better characterize aberrations to this system. Moreover, other neural regions dense with cannabinoid receptors (i.e., PFC, hippocampus) will be investigated. This work provides a basis for understanding stress impacts on the development of cognitive deficits observed in psychotic and anxiety disorders. Specifically, facilitation of eyblink conditioning complements research in humans with anxiety disorders. Broadly, understanding stress-related endocannabinoid dysregulation may provide insights into risks for, and the development of, psychopathology and uncover novel therapeutic targets with high translational power.